Centros judiciários de solução de conflitos e cidadania na comarca de Aracaju (2021-2022): desdobramentos para a realização da agenda 2030 da ONU - Soares, Wesley Andrade (2024)
The objective of this study is to understand the performance of the Center for Judicial Dispute Resolution and Citizenship of the State of Sergipe (CEJUSC) in the Aracaju District, as a potential guarantor of promoting the Rule of Law at the national level, providing access to justice for all, in accordance with Goal 16.3, embedded in Sustainable Development Goal (SDG) 16 - Peace, Justice, and Strong Institutions, which is part of the United Nations (UN) 2030 Agenda. Faced with the challenges that courts encounter in ensuring a fair judicial process, the symptoms of hyper-judicialization and a litigious culture are observed as indicators of a crisis. In contrast, the access to justice movement has contributed to the expansion and effectiveness of conflict resolution, mitigating the jurisdictional monopoly, resulting in institutional openness through the multi-door system, especially through pre-processual mediation and conciliation. One of the responses presented to address this crisis was Resolution No. 31/2015 of the Court of Justice of the State of Sergipe, which formalized judicial policies for the appropriate treatment of conflicts of interest. Thus, the specific objectives include describing the current crisis in the judiciary, then understanding the concept of access to justice and its realization through the multi-door system, as well as depicting the mediation and conciliation offered by CEJUSC in the Aracaju District as pre-processual forms of ensuring access to fair decisions, and finally evaluating possible ways to promote the Rule of Law, ensuring access to justice for all (Goal 16.3), in response to the UN 2030 Agenda. The adopted method is inductive, using quantitative analysis of process statistics in Brazil and qualitative techniques, including legislative studies, literature review, and document analysis. Therefore, the research aims to answer whether the access to justice is effectively achieved through alternative means of self-composition provided by CEJUSC in the Aracaju District. The desired result suggests that the existence and operation of CEJUSC bring efficient means of implementing access to justice, aligned with the promotion of the Rule of Law at the national level, ensuring access for all (Goal 16.3) of Sustainable Development Goal (SDG) 16 - Peace, Justice, and Strong Institutions of the UN 2030 Agenda.